THE CORRELATION BETWEEN THE USE OF STUDENT-CENTERED STRATEGIES AND STUDENTS’ UNDERSTANDING OF ENGLISH VOCABULARY TESTS IN ELECTRICAL ENGINEERING CLASSES - Paulina Novarita; Leny Saily Rahmah; Ramadhani, Fauzan (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
Effective vocabulary acquisition is essential for students to engage with technical materials and succeed in professional environments in vocational education. This study investigates the correlation between student-centered learning strategies and students’ understanding of English vocabulary in electrical engineering classes at SMKN 6 Bandung. Using a quantitative correlational method, data were collected from 36 tenth-grade electrical engineering students through a structured questionnaire and a vocabulary comprehension test. The instruments were validated, and reliability was confirmed with a Cronbach’s Alpha value of 0.729. To analyse the data, descriptive statistics and Pearson’s correlation were applied. The results revealed a strong positive correlation (r = 0.852, p < 0.001) between the implementation of student-centered strategies and students’ performance on the vocabulary test. Moreover, 69.5% of students scored at or above the 70th percentile, with 36.1% achieving perfect scores. These findings are consistent with Gagné’s instructional model, indicating that a structured and student-centered learning approach enhances cognitive processing and promotes better vocabulary retention. The study concludes that incorporating student-centered strategies in technical English instruction significantly improves student outcomes and recommends further research across diverse vocational disciplines to confirm the generalizability of these results.